Self-Regulated Strategy Instruction in Developmental Writing: A Design Research Project - MacArthur, Charles A.; Philippakos, Zoi A. (Community college review, 2013)
This design research project developed and evaluated curriculum for developmental writing classes in community colleges. The core of the curriculum was self-regulated strategy instruction, which has been shown to be effective with adolescents who are struggling as writers. In the curriculum, students learned strategies for planning, drafting, and revising compositions with an emphasis on using knowledge of text organization to guide planning and self-evaluation. In addition to specific writing strategies, students learned strategies for self-regulation. The study is part of a project that developed two levels of developmental writing courses, but only the lower level course is addressed in this article. This article reports findings from the first two cycles of implementation and revision. Over two semesters, the curriculum was implemented in eight classes taught by three instructors and revised after an analysis of quantitative and qualitative data. Substantial gains in writing achievement and motivation were found, especially in the second cycle. In addition to successes, the article discusses design challenges for the curriculum and professional development.